Leishmaniasis amongst TB patients from Kala-azar endemic areas admitted to Surya Kanto Hospital, Mymensingh (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Parasitic diseases and Tuberculosis were shown to be the risk factor for each other. Co-infection of visceral leishmaniasis and pulmonary tuberculosis are increasing public health problem now a days especially in developing countries. More than 81% of cases and deaths from TB are in developing countries and is aggravated by concurrency with parasitic diseases.Objective: To find out the occurrence of Leishmaniasis amongst Tuberculosis (TB) patients of Kala-azar endemic areas admitted to Surya Kanto (SK) Hospital, Mymensingh.Materials and Methods: This descriptive cross-sectional study was conducted at Infectious and Tropical Disease Department of Mymensingh Medical College Hospital, a tertiary referral hospital from January 2014 to Decmber 2016. A total 176 TB patients reported from Kala-azar endemic areas admitted were included. For confirmation of diagnosis all cases of TB were sent for Gene expert before that relevant tests like CBC (Complete Blood Count), X-ray chest, Mantoux test, Smear tests were done. After having confirmed all the TB cases were investigated for Kala-azar. Venous blood was collected for buffy coat and serum for ELISA. All 176 patients’ blood were tested with ICT(rK39) for VL. There after splenic aspiration were done with full aseptic preparation for only those who were ICT positive. Smears were prepared and viewed under microscope with 10x 100 magnification. After that all these cases were tested by ELISA.Results: A total of 176 TB patients were selected in this study of which 120(68.1%) were male and male-female ratio was 2.1: 1, the mean age was 43.06 years. Among patients 87.49% were within 16 to 60 years of age that means within productive age of life are infected more with TB. In terms of education 79.10%(139) patients were below Secondary level, that revealed the illiterate and or less literate people were affected more by TB. Maximum patient’s family 132(74.99%) had monthly income up to 10,000.00 BDT (125 US$)i.e. the poorer people of the area. Out of 176 patients Smear positive TB cases were 170(97.41%) but By Gene Xpert all 176 patients were found positive. The blood sample of 176 patients were tested with ICT rK39 and 12(6.81%) patients were found positive for leishmaniasis who suffered from TB. In splenic smear test 12 patients smear were examined of which 11(91.66%) were positive but by ELISA all 12(100%) were found positive.Conclusion: Visceral leishmaniasis and tuberculosis co-infection have drawn attention to the clinical aspect. In both diseases infection may remain dormant asymptomatic which may be related to immune suppression and may lead to active disease. This study has been able to find out leishmaniasis amongst tuberculosis patients from kala-azar endemic areas of Bangladesh.Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 3-8